2020
DOI: 10.1063/5.0025650
|View full text |Cite
|
Sign up to set email alerts
|

The effects of proton tunneling, 14N quadrupole coupling, and methyl internal rotations in the microwave spectrum of ethyl methyl amine

Abstract: The spectra of N-ethyl methyl amine, CH 3 (NH)CH 2 CH 3 , were measured using a molecular jet Fourier transform microwave spectrometer in the frequency range of 2 to 26.5 GHz. Splittings due to proton inversion tunneling, Coriolis coupling, 14 N quadrupole coupling, and methyl internal rotation were fully resolved. The experimentally deduced rotational constants are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
3
1
Order By: Relevance
“…35 This level was applied because it has yielded reliable rotational constants to guide the assignment in many of our previous investigations. [36][37][38] As expected from the proton magnetic resonance study on 2AF 2 and studies on similar molecules 9,34,39 two conformers were found at α = 0° (called syn) and 180° (called anti) on the potential energy curve illustrated in Figure 2. This is essentially the same as the energy difference found for the two conformers of 2-acetyl-5-methylfuran.…”
Section: Quantum Chemical Calculationssupporting
confidence: 63%
“…35 This level was applied because it has yielded reliable rotational constants to guide the assignment in many of our previous investigations. [36][37][38] As expected from the proton magnetic resonance study on 2AF 2 and studies on similar molecules 9,34,39 two conformers were found at α = 0° (called syn) and 180° (called anti) on the potential energy curve illustrated in Figure 2. This is essentially the same as the energy difference found for the two conformers of 2-acetyl-5-methylfuran.…”
Section: Quantum Chemical Calculationssupporting
confidence: 63%
“…Calculations at this level have given predicted equilibrium rotational constants Be which matched almost exactly the experimentally deduced rotational constants for 2,6-dimethylfluorobenzene [32]. For comparison, optimizations were also carried out at the ab initio MP2/6-311++G(d,p) level of theory, a level which yielded satisfactory results for many molecules of different classes of compounds in the literature [38][39][40][41][42]. Finally, we performed calculations at the MP2/6-31G(d,p) level, because it has provided rotational constants with values close to the experimental ones for many molecules containing a phenyl ring [43][44][45].…”
Section: Geometry Optimizationssupporting
confidence: 53%
“…In general, methyl groups attached to double bonds show barrier heights ranging from approximately 500 cm −1 to 750 cm −1 . This is much smaller than the values of about 1000 cm −1 found for methyl groups at the end of an alkyl chain [10,41,42]. We suspect the orbital interactions to be the reason.…”
Section: Propenyl Methyl Torsioncontrasting
confidence: 57%